SS – OCT angiography in retinal dystrophies with macular edema or cysts - El Matri, L.; Falfoul, Y.; Hassairi, A.; El Matri, K.; Nafaa, F.; Chebil, A. (Acta ophthalmologica (Oxford, England), 2017)
Purpose To analyze swept source optical coherence tomography angiography (SS – OCT‐A) findings in retinal dystrophies with macular edema or cysts. Methods Optical coherence tomography angiography and structural OCT were performed using a Swept‐source DRI OCT Triton (Topcon, Corporation, Japan) for 3 patients with retinitis pigmentosa and macular edema, 3 patients with enhanced S‐cone syndrome and 1 patient with X‐linked retinoschisis. Results In all patients, changes were more pronounced in the deep plexus where macular edema was more evident. Also, there was focal dislocation of the vascular network in correspondence with the serous intraretinal cysts. In patients with retinitis pigmentosa, capillary were visible at the top of the cysts. On the other hand, in case of X‐linked retinoschisis, we found wheel‐like cystoids cavities separated by apparently well‐vascularized walls with a good correspondence with structural en face OCT. Conclusions OCT‐A may provide information of great interest in inherited retinal dystrophies with macular edema or cysts. It reveals particular alterations above all located at the level of the deep capillary plexus and the choriocapillaris. Such information may be useful for phenotyping each case and understanding pathogenesis of cysts development in each dystrophy helping their future therapeutic management.